The emergence of León-Castile, c. 1065-1500 : essays presented to J.F. O'Callaghan - O'Callaghan, Joseph F. (Ashgate, 2015)
"The Emergence of León-Castile brings together the current research of colleagues, students and friends of Joseph F. O'Callaghan, a pioneer in the study of the kingdom of León-Castile. The essays focus on the politics, law and economy of León-Castile from its first great leap forward in the eleventh century to the civil strife of the fifteenth. No other volume in English allows the reader to trace the institutional development of the kingdom over several centuries. The collection underlines the fact that León-Castile was not a backwater but a sophisticated state that had an important influence on the development of medieval and renaissance Europe"--Provided by publisher.